The Wiley handbook of collaborative online learning and global engagement - Johnston, Deirdre D.; López Méndez, Irene (Wiley handbooks in Education, 2022)
"There is increasing interest in internationalizing the curriculum of colleges and universities. In nearly every academic discipline, we can recognize either the impact of globalization on our disciplinary knowledge and understanding, and/or the enrichment that multiple cultural perspectives and international contexts bring to our learning. Yet, multiple barriers exist that make it difficult for students to acquire global experiences. The COVID pandemic, beginning in spring of 2020, has curtailed study abroad experiences and made it difficult, if not impossible, to integrate global learning based on in-person exchange of students and faculty. However, the pandemic has also forced us to teach in new and innovative ways. The course accommodations compelled by the pandemic have increased both awareness of the pedagogical benefits, and the recognition of the necessity of integrating online learning opportunities, in conjunction with face-to-face teaching in order to facilitate global learning. We, therefore, virtual global learning more than ever before. Furthermore, in order to prepare students for a global society, and an increasingly global job market, we need to find ways to not only send students out to experience the world in person, but to also bring the world to our institutions"--